Characterization of the development of cowpea cultivars and of the quantity and quality of proteins in their grains - Gonçalves, Fabíola Vieira; Medici, Leonardo Oliveira; Fonseca, Marcos Paulo Santos da; Gaziola, Salete Aparecida; Lima, Gepatrik Rodrigues; Macedo, David Cabral; Azevedo, Ricardo Antunes (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate cowpea (Vigna unguiculata) cultivars regarding plant development and the quantity and quality of soluble proteins in their grains, for breeding purposes. The experiment was conducted in a greenhouse, in a completely randomized experimental design, with the Paulistinha, BRS Novaera, Epace 10, and BR 17-Gurguéia cultivars. Leaf area, shoot fresh and dry matter, leaf protein content, number of nodules, and nodule and root dry matter were evaluated. In mature grains, soluble fractions and soluble amino acids were also quantified, and the electrophoretic analysis was performed with protein denaturation. There were no differences between cultivars for the plant development variables. However, protein quantity and quality in the grain differed between cultivars. 'BRS Novaera' and 'BR 17-Gurguéia' showed a higher soluble protein content in their grains. 'BRS Novaera' exhibited higher contents of two soluble sulfur amino acids – methionine and cysteine – , not differing from 'BR 17-Gurguéia' regarding methionine content. Both cultivars presented protein band polymorphism, but BRS Novaera had an extra band for albumins. The BRS Novaera and BR 17-Gurguéia cultivars have the highest content of soluble proteins in their grains and the greatest protein polymorphism, which makes them suitable for improving the nutritional quality of cowpea.